Detection of circulating tumor human papillomavirus DNA before diagnosis of HPV‐positive head and neck cancer. Issue 7 (16th March 2022) - Rettig, Eleni M.; Faden, Daniel L.; Sandhu, Shaiba; Wong, Kristine; Faquin, William C.; Warinner, Chloe; Stephens, Phil; Kumar, Sunil; Kuperwasser, Charlotte; Richmon, Jeremy D.; Uppaluri, Ravindra; Varvares, Mark; et al.
Abstract: Human papillomavirus (HPV), most commonly HPV16, causes a growing subset of head and neck squamous cell carcinomas (HNSCCs), including the overwhelming majority of oropharynx squamous cell carcinomas in many developed countries. Circulating biomarkers for HPV‐positive HNSCC may allow for earlier diagnosis, with potential to decrease morbidity and mortality. This case‐control study evaluated whether circulating tumor HPV DNA (ctHPVDNA) is detectable in prediagnostic plasma from individuals later diagnosed with HPV‐positive HNSCC. Cases were participants in a hospital‐based research biobank with archived plasma collected ≥ 6 months before HNSCC diagnosis, and available archival tumor tissue for HPV testing. Controls were biobank participants without cancer or HPV‐related diagnoses, matched 10:1 to cases by sex, race, age and year of plasma collection. HPV DNA was detected in plasma and tumor tissue using a previously validated digital droplet PCR‐based assay that quantifies tumor‐tissue‐modified viral (TTMV) HPV DNA. Twelve HNSCC patients with median age of 68.5 years (range, 51‐87 years) were included. Ten (83.3%) had HPV16 DNA‐positive tumors. ctHPV16DNA was detected in prediagnostic plasma from 3 of 10 (30%) patients with HPV16‐positive tumors, including 3 of 7 (43%) patients with HPV16‐positive oropharynx tumors. The timing of the plasma collection was 19, 34 and 43 months before cancer diagnosis. None of the 100 matched controls had detectable ctHPV16DNA. This is the first report that ctHPV16 DNA is detectable at least several years before diagnosis of HPV16‐positive HNSCC for a subset of patients. Further investigation of ctHPV16DNA as a biomarker for early diagnosis of HPV16‐positive HNSCC is warranted. Abstract : What's new? Circulating tumor human papillomavirus (HPV) DNA (ctHPVDNA) is associated with tumor burden and response to treatment in HPV‐positive head and neck squamous cell carcinoma (HNSCC). In this case‐control study, ctHPVDNA was detected in plasma greater than 3 years prior to diagnosis of HPV‐positive HNSCC. This is the first study to demonstrate that ctHPVDNA is detectable prior to clinical development of an HPV‐positive cancer and thus, may allow for earlier diagnosis of HPV‐positive HNSCC.